Validation of the Malay version of the Diabetes Health Literacy Scale among Malaysian adults with type 2 diabetes mellitus - Pei Ling Ng; Wan Nor Arifin; Wan Mohd Izani Wan Mohamed; Rosnani Zakaria; Yee Cheng Kueh (PeerJ)
Background The aims of this study were to translate and adapt the Diabetes Health Literacy Scale (DHLS) to Malay, and to determine the validity and reliability of the Malay version of the DHLS (DHLS-M) among Malaysian adults with type 2 diabetes mellitus (T2DM). Methods The DHLS was translated and culturally adapted to Malay, followed by a cross-sectional study which was conducted using a self-administered questionnaire among the adults with T2DM in Hospital Universiti Sains Malaysia (USM). The participants were recruited by convenience sampling. Confirmatory factor analysis (CFA) and correlation analysis were performed. Results A total of 250 adults with T2DM participated in this study. The median age of the participants was 63.0 years old (IQR = 12.3) and most of the participants were male (51.2%). The final measurement model of DHLS-M with removal of one problematic item, fit the data well based on several fit indices: Relative chi-square (χ2/df) = 3.858, comparative fit index (CFI) = 0.981, Tucker–Lewis index (TLI) = 0.976. The composite reliability of the three subscales based on Raykov’s rho were 0.962, 0.836 and 0.828 respectively. The subscales of DHLS-M were significantly correlated with the Malay version of the Michigan Diabetes Knowledge Test (MDKT) (r = 0.26 to 0.31) and the Malay version of the short form Health Literacy Survey Questionnaire (HLS-SF12) (r = 0.43 to 0.66). Conclusion The DHLS-M, which consisted of three subscales and 13 items, is a valid and reliable instrument for measuring diabetes health literacy among adults with T2DM in Malaysia. Its validity was further strengthened by the convergent validity with the Malay version of the MDKT and the Malay version of the HLS-SF12.